What drives episodes of settlement fails in the government of Canada bond market? - Jean-Sébastien Fontaine; James Pinnington; Adrian Walton (Bank of Canada, 2017)
We study settlement fails for trades in the Government of Canada bond market. We find that settlement fails do not occur independently. Using a novel and comprehensive dataset, we examine three drivers of fails. First, we find that fails are more likely following the release of surprise macroeconomic news. Second, settlement fails are more likely for bonds with greater trading activity in the borrowing market. These findings suggest that the recirculation of bonds through long settlement chains is important for understanding fails. Third, fails are more likely when interest rates are low and when the cost for borrowing a bond is high, which is likely because of frictions acting as constraints on the price to borrow a bond. Together, the evidence suggests that improvements to the price mechanism in the borrowing market could improve the recirculation of scarce bonds and may improve the functioning of the bond market.
Keywords: E4; G1; G2; G21; L1; 330; Financial markets; Market structure and pricing; Payment clearing and settlement systems